Extracellular Histone H3 Induces Pyroptosis During Sepsis and May Act Through NOD2 and VSIG4/NLRP3 Pathways - Shi, Chun-xia; Wang, Yao; Chen, Qian; Jiao, Fang-zhou; Pei, Mao-hua; Gong, Zuo-jiong (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Histones could be released from the nucleus when stimulated. Increasing evidence has shown that extracellular histones are associated with a variety of inflammation and diseases. Nucleotide binding oligomerzation domain 2 (NOD2) belongs to the NOD like receptor (NLR) family and is reported to promote apoptosis and aggravate inflammatory response. And V-set and immunoglobulin domain containing 4 (VSIG4), a B7 family-related protein, has been confirmed to mediate transcriptional inhibition of nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3). However, little is known about the impact of extracellular histones on NOD2 or VSIG4 signal transduction. In this study, we aim to explore the effect and mechanism of extracellular histone H3 on pyroptosis. Aim: The purpose of this work was to investigate the mechanism of extracellular histone H3 on pyroptosis in sepsis. Methods: Lipopolysaccharide (LPS) and histone H3 were used to induce sepsis mice model and damage in ANA-1 macrophages. H3 antibody was applied to antagonize the effect of histone H3. NOD2 inhibitor NOD-IN-1 and VSIG4-siRNA were used to investigate the mechanism of histone H3 on pyroptosis. Enzyme linked immune sorbent assay (ELISA) was applied to detect the level of extracellular histone H3. Real-time PCR and Western blotting were employed to detect the key mRNA and protein levels. The pathology of tissues was detected. Results: The level of extracellular histone H3 was increased after LPS stimulation. The mRNA and protein levels of NLRP3, caspase-1, gasdermin D (GSDMD), interleukin (IL)-1β, IL-18 were increased in LPS group, but suppressed by H3 antibody. And the expression of NOD2, receptor-interacting protein 2 (RIP2) was elevated compared with control group. The expression of VSIG4 was inhibited by LPS and suppression of H3 promoted the protein level of VSIG4. H3 antibody alleviated pathological damages in tissues. Furthermore, the mRNA and protein levels of NOD2 in H3 group was higher compared with control group. The mRNA and protein levels of VSIG4 in H3 group was decreased compared with control group, but up-regulated by NOD-IN-1. Besides, the mRNA and protein levels of VSIG4 in NOD-IN-1 + VSIG4-siRNA group was elevated compared with VSIG4-siRNA group. Conclusions: Extracellular histone H3 induced by LPS could cause pyroptosis during sepsis via NOD2 and VSIG4/NLRP3 pathway.